The Used of Paci-Paci Leaves Extract Leucas sp. to Prevent Mycotic Disease - Sri Nuryati; M.A. Suparman; Y. Hadiroseyani (Jurnal Akuakultur Indonesia)
Injury of fish caused by handling of fry transportation and harvesting could impact mycosis. Effort on controlling by using chemotherapeutic could impact on pollution of environtment and even  carcinogenic effect. One of alternative substances  can be used in both preventing and controlling safely is paci-paci, Leucas sp. This method based on phytopharmacy.  The aim of this research is to test the prevention of paci-paci leaves extract to mycotic disease .  This research used five treatments: possitive control; the doses of paci-paci  extract were 0 gr/l (negative control); 0.5 gr/l; 1 gr/l and 1.5 gr/l by using the gurami, Osphronemus gouramy Lac. That was measuring 7-9 cm. The method that was used is the short-term submersion (short baths) for 24 hours.  Paci-paci extract can reduced the fungal infection and hindered the growth of Saprolegnia sp. colonies.  Descriptively, the paci-paci extract (the treatment of the extract 0.5 gr/l; 1 gr/l; 1.5 gr/l) could prevent the Saprolegnia sp. infection with the successive prevalence 33.3 %; 22.2 %; 0 %.